Marketing for tourism - Holloway, J. Christopher; Robinson, C. (Harlow, Essex : Longman, 1995)
This book is about: The marketing perspective; Marketing planning; Marketing research and its applications in tourism; Tourism product policy; Pricing the product; marketing communications; ...
Keywords: Marketing; Tourism; Tourism -- Marketing